Post-shipment financial flows in supply chains: A study of small- to medium-sized enterprise importers - Francois Schutte; Wesley Niemann; Theuns Kotzé (Journal of Transport and Supply Chain Management, 2019)
Background: Global sourcing has impacted inventory levels, lead times and the availability of working capital, affecting the standard financial flow of a supply chain. Poorly managing the link between the financial and physical supply chains could therefore lead to unnecessarily high inventory investments or to a short supply of inventory, affecting cash flow, working capital, sales and, subsequently, a firm’s profitability. Objectives: The aim of this generic qualitative study was to explore how firms manage their financial supply chain alongside their physical supply chain. Method: Data were collected from 12 semi-structured interviews with senior managers across six small- to medium-sized enterprise (SME) importing firms in various industries. Results: The research finds that the buyer is the driver of both upstream and downstream financial supply chain management (FSCM) as SME importers in Gauteng are proactively managing their financial alongside their physical supply chains. Through the continuous evaluation of sourcing strategies, exchange rate risk management strategies and inventory investment management strategies, firms can align their physical and financial supply chains. Conclusion: This study highlights the lead time and disruption risks and costs of global sourcing and identifies FSCM tools that can be used to alleviate the financial burden associated with long lead times.